1998
DOI: 10.2466/pms.1998.87.3.817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consumption of Snacks on Simulated Driving

Abstract: The present study investigated the effects of snacks on simulated driving for 24 volunteers who carried out a driving task three times. On each occasion a presnack baseline of 1 hr. of driving was taken. The snack conditions were (a) no snack (b) a 65 g-filled chocolate bar, and (c) an equicaloric snack of cheese and biscuits. Following the snack the volunteers then carried out another hour of driving. Analysis showed that following consumption of the chocolate the volunteers drove more carefully and hit the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Previous studies have found that consumption of breakfast, in particular breakfast cereals, is associated with better physical and mental well-being and subjective health [30,31]. Our results are also consistent with the traditional view that eating a healthy breakfast is linked to lower mental distress, fewer depressive symptoms, positive mood and improved quality of life [32]. …”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found that consumption of breakfast, in particular breakfast cereals, is associated with better physical and mental well-being and subjective health [30,31]. Our results are also consistent with the traditional view that eating a healthy breakfast is linked to lower mental distress, fewer depressive symptoms, positive mood and improved quality of life [32]. …”
Section: Discussionsupporting
confidence: 90%
“…This has been interpreted in terms of a beneficial effect of glucose on a brain deprived of glucose by the nighttime fast. Glucose may have other benefits and we have found that it improves simulated driving performance (Smith & Rich, 1998). Again, other laboratories have also demonstrated beneficial effects of breakfast consumption (e.g.…”
Section: Effects Of Food and Drink On Performance And Moodsupporting
confidence: 60%
“…Such recommendations would perhaps be more realistic than simply prohibiting the activity, as we should also acknowledge potential beneficial effects of eating and drinking on task performance. For instance, the NHTSA survey found that 17% of drivers fight fatigue by taking a coffee or a soft drink, and research suggests that sugary snacks or drinks can indeed help stave off sleepiness and improve lane-keeping performance (Horne and Baulk, 2004;Parkes et al, 2001;Smith and Rich, 1998).…”
Section: Discussionmentioning
confidence: 99%